Arjun Sharma - Jamnapur, Bihar India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Arjun Sharma is the Village President and Chairman of the farmer cooperative PACS (Primary Agricultural Cooperative Society) in the village of Jamnapur, India. Arjun describes in the video how the cooperative supports farmers through different activities such as saving schemes, low-interest rate loans to peasants who want to develop their farms and adapt to climate change. Members of PACS can also insure their crops, which the government urges the farmers to do every season. From the cooperative everybody earns and eats, Arjun Sharma explains.